Enhancing nursing documentation in Kazakhstan: assessing utilization and standardization for improving patient care - Sydykova, Bibinur; Smailova, Dariga; Khismetova, Zaituna; Brimzhanova, Marzhan; Baigozhina, Zaure; Hosseini, Hengameh; Latypova, Natalya; Izmailovich, Marina (Frontiers in Public Health, 2023)
Background and Aim: This article stresses the importance of comprehensive nursing documentation in scientific medicine and discusses the adoption of standardized terminologies in Europe. The study also presents findings from a cross-sectional study conducted in Kazakhstan, assessing the utilization of standard operating procedures and nursing documentation in various clinical scenarios. The aim was evaluate the level of use of the form of nursing documentation and Standard Operating Procedure within the framework of reforming the Republic of Kazakhstan. Materials and Methods: During the period from December 2021 to February 2022, a cross-sectional study was conducted in Kazakhstan, involving a randomly selected sample of nurses with technical and vocational education as well as those with applied/academic baccalaureate degrees in nursing. Results: In this cross-sectional study of 2,263 female nurses, 75.3% were nurse practitioners, and 44% held the highest qualification category. Awareness levels varied, with around 64.7% aware of the pilot program for care services, 65.8% aware of the deputy head position, and 73.8% familiar with the "extended practice nurse" role. Only 55.2% knew about the International Clinical Nursing Classification, and 54.5% observed changes in their nursing approach due to education. The limb edema measurement checklist was not used by the majority (88.4%) of respondents, and 68% did not utilize the antibiotic susceptibility testing checklist. Various other checklists and algorithms had limited utilization, with percentages ranging from 9.1% to 69.3%, indicating varying levels of adoption among participants. For assisting children with cerebral palsy, the "Assessment of hand use capacity according to the MACS classification system" was utilized by 9.1%, while 90.9% did not employ it. In the context of communication, 30.7% of the respondents utilized the "Algorithm of actions of a medical registrar when communicating with a patient," while 69.3% did not use it. These findings highlight variable adoption rates among participants for these medical procedures and protocols. Conclusion: In Kazakhstan, nursing documentation forms and Standard Operating Procedures face challenges and limited utilization, but their implementation has shown positive impacts on patient care and healthcare outcomes. Overcoming resistance to change, increasing awareness, and addressing resource constraints are essential for further improvement.